The Chapter of the “Marriage of Polytheists” in the Book of Al-Omdah Lil Omah Fi Mathahib Al-Aemah Fi Al-Mabahib Al-Fikhia Wal Asrar Al-Shariyah by Imam Yahya bin Hamza Al-Hosaini - Hazbar, Abduljalil Abdullah Ahmed (Journal of Islamic Sciences, 2023)
The idea of the research was based on selecting a chapter from the chapters of the doctoral dissertation, which is an investigation and study of one of the Yemeni manuscripts entitled: The Omda for the Nation in the Doctrines of the Imams in the Jurisprudential Investigation and the Sharia Secrets of Imam Yahya bin Hamza Al-Husseini (T: 749 AH) - study and investigation - from the beginning of the chapter Marriage - to the end of the second book) Introduction to obtaining a doctorate degree in Islamic studies (comparative jurisprudence) and the author chose to a chapter from the marriage book (marriage to unbelievers, and he explains all about these marriages and he commented on what he saw suitable and put a translation at the forefront of the research, to introduce the author and his scientific life.
Keywords: Marriage; Shirk; Shafi'i; Hanafi; Maliki; Hadawi; Dowry Inheritance